Community Curation and Expert Curation of Human Long Noncoding RNAs with LncRNAWiki and LncBook. Issue 1 (20th June 2019) - Ma, Lina; Cao, Jiabao; Liu, Lin; Li, Zhao; Shireen, Huma; Pervaiz, Nashaiman; Batool, Fatima; Raza, Rabail Z.; Zou, Dong; Bao, Yiming; Abbasi, Amir A.; Zhang, Zhang
Abstract: In recent years, the number of human long noncoding RNAs (lncRNAs) that have been identified has increased exponentially. However, these lncRNAs are poorly annotated compared to protein‐coding genes, posing great challenges for a better understanding of their functional significance and elucidating their complex functioning molecular mechanisms. Here we employ both community and expert curation to yield a comprehensive collection of human lncRNAs and their annotations. Specifically, LncRNAWiki (http://lncrna.big.ac.cn/index.php/Main_Page ) uses a wiki‐based community curation model, thus showing great promise in dealing with the flood of biological knowledge, while LncBook (http://bigd.big.ac.cn/lncbook ) is an expert curation–based database that provides a complement to LncRNAWiki. LncBook features a comprehensive collection of human lncRNAs and a systematic curation of lncRNAs by multi‐omics data integration, functional annotation, and disease association. These protocols provide step‐by‐step instructions on how to browse and search a specific lncRNA and how to obtain a range of related information including expression, methylation, variation, function, and disease association. © 2019 by John Wiley & Sons, Inc.